2008
DOI: 10.3324/haematol.12955
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune conditions and chronic infections in chronic lymphocytic leukemia patients at diagnosis are associated with unmutated IgVH genes

Abstract: Few data are available concerning the prevalence of autoimmune disease or chronic infections in chronic lymphocytic leukemia patients at diagnosis as well as their clinical outcome. We studied the frequency of such chronic conditions in relation to prognostic markers. A history of autoimmune disease or chronic infection was found in 21% of 186 chronic lymphocytic leukemia patients (12% in autoimmune diseases, 9% in chronic infections). Patients with a history of chronic stimulation were more likely to have unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…Nearly all of our patients had already received several lines of treatment either for progressive CLL, autoimmune cytopenia or both. As previously reported in CLL patients developing AIHA [13,14], they exhibited in most cases adverse prognostic factors, namely unmutated IGHV and 11q deletion. BR therapy led to a prolonged control of AIHA in 80% of cases, although the complete response rate for AIHA was rather low.…”
Section: Discussionsupporting
confidence: 71%
“…Nearly all of our patients had already received several lines of treatment either for progressive CLL, autoimmune cytopenia or both. As previously reported in CLL patients developing AIHA [13,14], they exhibited in most cases adverse prognostic factors, namely unmutated IGHV and 11q deletion. BR therapy led to a prolonged control of AIHA in 80% of cases, although the complete response rate for AIHA was rather low.…”
Section: Discussionsupporting
confidence: 71%
“…Ͻ 12 months) correlated with the risk of developing autoimmune cytopenia. More recently, some studies have found an association between autoimmune cytopenia and unfavorable biomarkers, including unmutated IGHV genes, 7,[31][32][33] high expression of CD38 34 or ZAP-70, 7,35 and increased B2M serum levels. 28,29,32 In our series we also found a correlation between increased serum B2M levels, high ZAP-70 or CD38 expression, and autoimmune cytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Cuttner and colleagues analyzed HL and CLL patients with the control group. Other studies reported 39% AI among MALT lymphoma patients [11], and 16% and 11.8%, respectively, in CLL [12,21]. In all three studies, AI patients with malignant diseases were predominantly women.…”
Section: Discussionmentioning
confidence: 90%
“…In total, 574 patients with malignant lymphoma were diagnosed at the unit between 2001 and 2005. Of note, this number does not include patients with chronic lymphocytic leukemia (CLL) and MALT lymphoma since results for these entities were published elsewhere [11,12]. Of 574 patients, 94 were excluded from the analysis because of underlying immunosuppression (HIV positivity, post transplant lymphoproliferative disorder, common variable immunodeficiency) or because they were classified as primary CNS lymphomas.…”
Section: Patientsmentioning
confidence: 99%